PENGARUH KUALITAS PELAYANAN, HARGA DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG DI E-COMMERCE SHOPEE (STUDI KASUS MAHASISWA GALILEO BATAM) - Ziliwu, Tostiar Elmanuel; Riki, Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This writing aims to determine the effect of Service Quality, Price and Trust on Repurchase Interest in e-commerce shopee. The type of research used is the descriptive analysis method, which provides an overview of the variables about the research object being studied and then draws conclusions. The research object which is the independent variable is Service Quality (X1). Price (X2), Trust (X3) and Repurchase Interest (Y) as the dependent variable. The population of this study were STIE Galileo students, Batam. The method used for sampling is purposive sampling technique, meaning that the sampling technique and determination of the sample are determined by the researcher. The results of research data processing show that there is an influence of service quality, price and trust on repurchase intention at e-commerce shopee. R square 82.4% of these results it can be concluded that the variables Service Quality (X1), Price (X2) and Trust (X3), simultaneously affect Repurchase Interest (Y). while 17.6% is influenced by other variables outside this regression equation or variables not examined by the author.